2011
DOI: 10.5054/tq.2011.247705
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Working Memory Capacity and Content Familiarity on Literal and Inferential Comprehension in L2 Reading

Abstract: This study examines the effects of working memory capacity and content familiarity on literal and inferential comprehension in second language (L2) reading. Participants were 62 Turkish university students with an advanced English proficiency level. Working memory capacity was measured through a computerized version of a reading span test, whereas content familiarity was achieved through nativization of a narrative, that is, textual and contextual modification to reflect the reader's own culture. After complet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(83 citation statements)
references
References 103 publications
5
72
3
Order By: Relevance
“…In addition, the RST scores in English were found to correlate with RST scores in the L1 (Alptekin & Erçetin, 2010), in line with previous research indicating that WM capacity is independent of particular languages (Osaka & Osaka, 1992;Osaka, Osaka, & Groner, 1993). The test scores were also found to correlate with reading comprehension scores (Alptekin & Erçetin, 2011), providing evidence for the predictive validity of the test. on the questions Mayer (2009) presented, in terms of content, wording, and design.…”
Section: Transfer Testsupporting
confidence: 73%
See 1 more Smart Citation
“…In addition, the RST scores in English were found to correlate with RST scores in the L1 (Alptekin & Erçetin, 2010), in line with previous research indicating that WM capacity is independent of particular languages (Osaka & Osaka, 1992;Osaka, Osaka, & Groner, 1993). The test scores were also found to correlate with reading comprehension scores (Alptekin & Erçetin, 2011), providing evidence for the predictive validity of the test. on the questions Mayer (2009) presented, in terms of content, wording, and design.…”
Section: Transfer Testsupporting
confidence: 73%
“…This could be attributed to text length and self-paced presentation. In other words, the length of the text being much shorter in the current study compared to the previous studies (e.g., Alptekin & Erçetin, 2011) and the self-paced nature of the task might have increased the chances of reviewing for the reading groups thereby balancing both their performance levels and their perceived amounts of cognitive load. Such an assumption appears to be plausible given that the modality effect may disappear under self-pacing (e.g., Sweller et al, 2011;Wouters et al, 2009).…”
Section: Discussionmentioning
confidence: 69%
“…It is necessary to mention that teachers have a fundamental role in teaching grammar and vocabulary (literal comprehension skills of parsing and lexical access, respectively), so that learners can devote more attentional resources to higher-level processes of inferential comprehension (Alptekin and Erçetin, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…In order to construct the microstructure of the text, inferences are necessary to form a coherent microstructure (Alptekin and Erçetin, 2011;Kinstch and van Dijk, 1978;Kinstch and Rawson, 2007). The microstrucure is not "loose in itself"; it must belong into to higher-order units, namely the macrostructure of the text.…”
Section: On Inferencesmentioning
confidence: 99%
“…Chiappe and Siegel 1999). But on the other hand, some researchers have revealed that NL skills enhance the development of reading skills in the FL in domains such as word readings, spelling, vocabulary, reading comprehension and reading strategies (Alptekin and Ercetin 2011;Nation 2001). Even more pointedly, they have suggested that FL learners need only have reached a certain vocabulary threshold (about 8000 words) for comprehension to increase naturally when there is cognate support from their NL, that is, when the NL and FL are from the same root language (Martinez and Murphy 2011).…”
Section: Introductionmentioning
confidence: 98%